1962
DOI: 10.1001/jama.1962.03050010003001
|View full text |Cite
|
Sign up to set email alerts
|

Raynaud's Phenomenon

Abstract: Of 66 patients exhibiting Raynaud's phenomenon who have been followed from 1 to 25 years, 20 exhibited peripheral vascular disease, 35 were diagnosed as having collagen disease, 7 showed evidence of vasomotor hyperactivity, and 4 showed abnormal clumping of red blood cells or precipitation of globulin. Only 18 patients were subjected to bilateral dorsal sympathectomy. The failure rate is not so much due to the recurrence of sympathetic activity, but to case selection. Many patients have been erroneously subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1964
1964
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The first group consisted of 10 patients, aged 22-56 (mean, 42) with Raynaud's disease. Classic Raynaud's phenomenon was defined as intermittent pain or paresthesias of symmetrical digits on emotional stress or exposure to cold with the sequential development of the characteristic color changes of pallor, cyanosis, and then rubor (8,9). Incomplete Raynaud's phenomenon was defined as intermittent development of one of the characteristic color changes on emotional stress or exposure to cold with or without the pain or 1Abbreviation used in this paper: LES All patients were studied while resting quietly in the supine position after an 8 hr fasting period.…”
Section: Methodsmentioning
confidence: 99%
“…The first group consisted of 10 patients, aged 22-56 (mean, 42) with Raynaud's disease. Classic Raynaud's phenomenon was defined as intermittent pain or paresthesias of symmetrical digits on emotional stress or exposure to cold with the sequential development of the characteristic color changes of pallor, cyanosis, and then rubor (8,9). Incomplete Raynaud's phenomenon was defined as intermittent development of one of the characteristic color changes on emotional stress or exposure to cold with or without the pain or 1Abbreviation used in this paper: LES All patients were studied while resting quietly in the supine position after an 8 hr fasting period.…”
Section: Methodsmentioning
confidence: 99%
“…In varying degrees of severity it exists in between 5-10% of the population (Blunt & Porter, 1981) but in the vast majority of cases these symptoms require only a minimal change in the patient's life style to be relieved (for example, cold avoidance, wearing gloves). The disease, however, may be severe, especially when the syndrome occurs in association with a connective tissue disorder; pain, digital ulceration and even gangrene can result (De Takatas & Fowler, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…Intra-arterial reserpine (Elbaor et al, 1971), oral vasodilators , sympathectomy (De Takatas & Fowler, 1962), fibrinolytic enhancement (Jarrett et al, 1981) and plasma exchange (Zahavi et al, 1980) have been used with varying effect. Recently it has been shown that the symptoms of Raynaud's syndrome improve after treatment with the prostaglandins PGE1 (Clifford et al, 1980) and prostacyclin (PGI2;Belch et al, 1981), but both of these drugs require parental administration with the patients admitted to hospital for the duration of the infusion.…”
Section: Introductionmentioning
confidence: 99%
“…These estimates, however, conflict with prevalence estimates that can be derived from determining the proportion of SSc patients among groups of patients with Raynaud's phenomenon described in the literature (up to 37%) (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and, in turn, from estimating the percentage of RP patients among the general population, believed by several authors to range from 10% to 20% (15)(16)(17)(18)(19). Such calculations yield SSc prevalence rates of approximately 3,000-6,OOO per 100,000, which greatly contrasts with the highest prevalence of 13.8 per 100,000, as cited above (7).…”
mentioning
confidence: 99%